Manajemen Usaha Salon Kecantikan Di Kota Pekanbaru - permatasari, Riga Dilta (RC-INSTITUT, 2019)
This research is backed by the development of business beauty salon in the city of Pekanbaru. The purpose of this research is (1) Planning/Planning, (2) Organizing/Organizing, (3) Actuating/Implementing, and (4) Controlling/supervision. This type of research is quantitative descriptive, with the survey method. The population in this research is the owner of a salon that totals 10 people. Sampling techniques are a total sampling. The data analysis technique is a percentage. Data collection techniques are conducted using questionnaires with Likert scales. Based on the results of this study, advice to the leader of the salon in Kota Pekanbaru is to maintain the management that has been very good. And can improve from several sub indicators through basic principles of management as well as knowing the function of managing the business to run the salon can develop, forward to the wishes and expectations of the management.